AKTIVITAS MUKOLITIK IN VITRO EKSTRAK ETANOLIK HERBA MENIRAN (Phyllanthus niruri L) TERHADAP MUKOSA USUS SAPI - yulias ninik windriyati; mimik murrukmihadi; nissa ratna junita (Universitas Wahid Hasyim Semarang, 2007)
ABSTRACTPhyllanthus niruri L has been traditionally used by Indonesian people to treat cough. However, scientific basic of using this plant as mucolytic agent is still less observed. The aim of this research is to evaluate in vitro mucolytic activity of ethanol extract of P. niruri against bovine bowels mucose. In vitro mucolytic activity of P. niruri was tested through method as like as Haslinda (1999) and Setyawati (2004). Ethanol extract of P. niruri at various concentrations 0,25; 0,5; 0,75; 1,0; and 1,25% b/v mixed with mucose solution 50% b/v in fosfat buffer pH 7. The solution incubated at 37ºC during 30 minute. Solutions viscosity measured by stormer viscometer and evaluated its fluid flow properties. Negative control was mucosa solution without extract and positive control was asetilsistein. Mucolytic activity was shown by a concentration of extract which decrease viscosity of mucose solution. Ethanol extract of P. niruri had mucolytic activity againts bovine bowels mucose which decrease viscocity of mucose. However, statistically there was no difference between various concentrations of ethanol extract to mucolytic activity. Ethanol extract of P. niruri at concentrations 0,25; 0,5; and 0,75% in mucose solution had fluid flow properties thiksotropi pseudoplastic and at concentrations 1,0 and 1,25% had fluid flow properties pseudoplastic.